Screening and Identification of The 16S rRNA Sequence Phylogeny of Fibrinolytic Bacteria in Shrimp Paste - Sari, Maharani Puspita; Toto Poernomo, Achmad; Prawita, Amiruddin (Universitas Airlangga, 2022)
Petis was one of the fermentation products made with marine creatures such as fish or shrimp. Fibrinolytic enzymes in some fermentation foods from marine creatures were discovered. Screening of bacteria that produced fibrinolytic enzymes used six petis samples from different home industries. The isolation of samples was performed using the Skim Milk Agar proteolytic test and fibrin plate test. Identification of the bacteria was performed with a gram staining test and 16S rRNA sequencing method. The sample was diluted with NaCl 0.9% up to 10^-7, then inoculated on the SMA media and incubated at 37ºC for 24 hours. All samples showed proteolytic activity, indicated by a clear zone around the colony. Seventeen proteolytic bacterial isolates were tested for fibrinolytic activity with fibrin plates and then incubated at 37ºC for 24 hours. The seventeen isolates showed positive results for fibrinolytic activity, with the highest fibrinolytic index being P3c. The P3c bacterial isolate was identified using 16S rRNA gene sequencing. The result of the identification revealed that the bacteria with strong fibrinolytic activity was Bacillus flexus.Keywords: Fibrinolytic Enzyme, Petis, Screening, Identification, Bacillus flexus